USM VICE-CHANCELLOR PAYS COURTESY CALL ON INDONESIAN MINISTER TO DISCUSS RESEARCH COOPERATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
JAKARTA, INDONESIA, 28 September 2015 – The ViceChancellor of Universiti Sains Malaysia (USM) Professor Dato’ Dr. Omar Osman and Deputy ViceChancellor (Research and Innovation) Professor Dr. Muhamad Jantan paid a courtesy call on the Minister of Research, Technology and Higher Education, Republic of Indonesia, Professor Dr. H. Mohamad Nasir at the latter’s office here recently.